Janus bifunctional periodic mesoporous organosilica. Issue 1 (8th December 2021) - Vafaeezadeh, Majid; Weber, Kristin; Demchenko, Anna; Lösch, Philipp; Breuninger, Paul; Lösch, Andrea; Kopnarski, Michael; Antonyuk, Sergiy; Kleist, Wolfgang; Thiel, Werner R.
Abstract : A Janus strategy was employed for the synthesis of a novel and multidisciplinary organic–inorganic hybrid periodic mesoporous organosilica with the ability for formation of Pickering emulsion. Abstract : Synthesis of a Janus periodic mesoporous organosilica material (JPMO) is presented here. In this strategy, the surface of the hollow silica material was selectively functionalized with two different bridged organic–inorganic hybrid groups. It was found that the resulting bifunctional material is able to form a stable Pickering emulsion. This new type of PMO material may be suitable for widespread applications in various fields related to material science and catalysis.